A plastic-degrading composite microbial preparation and preparation method thereof
By using a variety of thermophilic and non-thermophilic microorganisms and solid adsorption carriers in plastic degradation composite microbial preparations, the problem of slow microbial degradation speed and difficulty in maintaining degradation efficiency is solved, and the efficient and highly adaptable plastic degradation effect is achieved.
Patent Information
- Application Number
- CN202411639478.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
In the prior art, microbial degradation rates of plastics are slower and it is difficult to maintain their degradation efficiency in a natural environment.
A plastic degradation composite microbial preparation is used, which includes a variety of thermophilic and non-thermophilic microorganisms, such as Bacillus stearothermophilus, Thermophilus thermophilus, Bacillus amidophilus, etc. Combined with solid adsorption carriers such as molecular sieve, TiO2, ZnO, Cu2O and Fe3O4, the synergistic effect of liquid mixed bacteria and solid adsorption carriers can improve the degradation efficiency and adapt to different temperature conditions.
It significantly improves the degradation efficiency of plastics, can maintain a high degradation efficiency under different temperature conditions, and extends the service life of the formulation in natural environment.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of soil pollution remediation, and specifically relates to a plastic-degrading composite microbial preparation and a preparation method thereof. Background Art
[0002] Plastic mulch is widely used in crop planting, which has the advantages of increasing soil temperature, retaining soil moisture, improving soil structure, and increasing crop yield and quality. However, as the coverage rate of plastic mulch on crops increases, after a season of agricultural activities, the film is not recycled due to its thin thickness, and a large amount of film remains in the soil.
[0003] The accumulation of discarded agricultural film fragments in agricultural soil can lead to serious consequences, as follows:
[0004] 1) It will destroy the soil structure of farmland, hinder the flow of water, lead to uneven soil moisture, cause compaction, and reduce the drought resistance and water retention of the soil; in addition, the large-sized agricultural film fragments remaining in the soil will directly hinder the extension of crop roots, resulting in underdeveloped plant roots and weakened water and fertilizer absorption capacity, all of which will affect the yield and quality of crops.
[0005] 2) After partial degradation, plastic mulch residues will produce organic compounds and microplastics with a particle size of ≤5mm. The long-term accumulation of these substances will affect plant growth and the structure and diversity of microbial communities in the soil.
[0006] 3) Nano-microplastics may enter plant tissues, posing a risk of entering the food chain.
[0007] At present, the most widely used agricultural plastic mulch material in my country is polyethylene (PE), which is a type of thermoplastic resin obtained by polymerization of ethylene monomers. It has the advantages of good stability, electrical insulation, low temperature resistance, odorlessness and non-toxicity, strong hydrophobicity, and strong acid and alkali resistance. Because of these characteristics, polyethylene is extremely difficult to degrade in the soil. Researchers have studied the degradation of polyethylene in the soil by C 14 Tracking and monitoring the degradation of labeled polyethylene mulch found that its degradation rate was only 0.2% to 0.5% after 10 years of landfill. Existing plastics can be degraded mainly in two ways: non-biodegradation and biodegradation. Among them, non-biodegradation refers to the change of physical and chemical properties of hydrocarbons in plastics due to environmental factors such as light, mechanical force, air or temperature. Biodegradation refers to the formation of a "biofilm" (or "plastic circle") on the surface of discarded plastics by microorganisms using their own adsorption, and then participating in a series of biological oxidation reactions by secreting related enzymes to finally decompose high-molecular plastic polymers into CH4, H2O, CO2, biomass and inorganic compounds.
[0008] Biodegradable plastics have the advantages of being environmentally friendly, biosafe, and reducing landfill and incineration. However, in actual application, the rate of microbial degradation is slow and it takes a long time to observe the degradation effect. In addition, many microorganisms that can degrade plastics need to react in a specific environment and it is difficult to maintain their degradation efficiency in the natural environment, which seriously affects the development of biodegradable plastics. Summary of the invention
[0009] The purpose of the present invention is to provide a plastic-degrading composite microbial preparation and a preparation method thereof, so as to solve the problems that the degradation efficiency is slow in the above-mentioned process of biodegrading plastics using microorganisms, and that it is difficult for microorganisms to maintain their degradation efficiency in the natural environment.
[0010] In order to achieve the above object, the present invention provides the following technical solutions:
[0011] The first aspect of the present invention provides a plastic-degrading composite microbial preparation, which comprises mixed bacteria and a solid adsorption carrier;
[0012] The raw materials of the mixed bacteria include Bacillus stearothermophilus, Thermus thermophilus, Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens, and Saccharomyces lipolytica;
[0013] The solid adsorption carrier includes a molecular sieve and TiO2, ZnO, Cu2O and Fe3O4 distributed in the molecular sieve, wherein the mass ratio of TiO2, ZnO, Cu2O and Fe3O4 is 1:1: (0.5-0.8): (0.2-0.4).
[0014] Preferably, the water content of the composite microbial preparation is less than 28%, and the total bacterial count is greater than 2.5×10 9 cfu / g.
[0015] In view of the problem that the degradation rate of microbial degradation of plastics in the existing technology is slow, the present invention specifically designs the types of microorganisms. The microorganisms in the present invention include Bacillus stearothermophilus, Thermus thermophilus, Bacillus amyloliquefaciens, Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens, and Saccharomyces lipolytica. The synergistic effect of multiple microorganisms improves the degradation efficiency of the preparation on plastics. Analysis of the reasons: Bacillus stearothermophilus can usually produce a variety of enzymes, such as lipase, protease, etc., which can decompose fat and protein substances. Under high temperature conditions, it can help to quickly decompose the aliphatic polyester components in plastics. Thermus thermophilus can survive and be active in high temperature environments. It can produce a variety of heat-stable enzymes, which help to degrade heat-resistant components in plastics. Bacillus amyloliquefaciens can produce a variety of enzymes such as α-amylase, which helps to decompose starch-based components or other carbohydrates in plastics. Bacillus amyloliquefaciens is also a bacterium that produces amylase. It can provide an easily accessible carbon source for other microorganisms by decomposing the starch matrix in plastics. Bacillus proteolyticus can produce proteases, which help to decompose proteins or other peptide chain structures contained in plastics. Bacillus ferrooxidans can reduce iron ions and may participate in the electron transfer process, which helps the redox reaction in the degradation process of plastics and accelerates degradation. Saccharomyces lipolytica can produce a variety of enzymes, especially lipases, which can decompose fatty acids and other lipid substances, and help degrade the aliphatic part of plastics. The enzymes produced by different microorganisms used in the present invention can decompose different components of plastics, such as fats, proteins, carbohydrates, etc., so as to achieve comprehensive degradation. Some microorganisms may produce byproducts that help other microorganisms grow, or change environmental conditions (such as pH value) to facilitate the activities of other microorganisms. Each microorganism occupies a different ecological niche, some are suitable for acting in the early stage, and some play a greater role in the later stage, forming an orderly degradation process. Therefore, these microbial strains can work synergistically to promote the efficient degradation of plastics.
[0016] The present invention continues to study and find that plastic degradation composite microbial preparations are mostly used outdoors. The outdoor environment is difficult to control. There are four seasons in different regions. The maximum temperature in summer can reach about 45 degrees Celsius, and the maximum temperature in winter can be as low as -30 degrees Celsius, or even lower. A single microbial agent is easily affected by the environment. In response to this problem, first of all, the present invention starts from the design of the components of the microbial agent, including thermophilic bacteria and non-thermophilic bacteria. Thermophilic bacteria usually show the best activity at higher temperatures (usually above 50°C). Their enzymes have high thermal stability and can remain active at high temperatures, thereby ensuring the degradation efficiency under high temperature environments. The enzymes produced by non-thermophilic bacteria are more active at lower temperatures, and their enzyme activity will not be significantly reduced due to temperature drops. Under high temperature conditions, the metabolic activities of thermophilic bacteria may produce some intermediates or by-products, which can provide nutrients for non-thermophilic bacteria. Vice versa, the metabolic activities of non-thermophilic bacteria at lower temperatures may also create more favorable conditions for thermophilic bacteria. This mechanism of mutual utilization helps to improve the metabolic efficiency of the entire system, thereby improving the efficiency of plastic degradation. Secondly, in the present invention, the liquid mixed bacteria are adsorbed on the solid adsorption carrier, and the molecular sieve therein can provide a physical barrier for the microorganisms, reduce the influence of the external environment (such as temperature change, water loss, etc.) on the microorganisms, thereby protecting the activity of the microorganisms. This protective effect is particularly important under high or low temperature conditions, because extreme temperatures may directly damage the cell structure of the microorganisms. The solid adsorption carrier can also create a relatively stable microenvironment for the microorganisms. Even if the external environment temperature changes, the microenvironment inside the carrier can still maintain a relatively constant state, which helps the microorganisms maintain their metabolic activities. In addition, the presence of the solid adsorption carrier can also promote the attachment of microorganisms to the plastic surface, increase the contact area between the microorganism and the plastic matrix, and help improve the degradation efficiency. In addition, the microorganisms attached to the carrier are more likely to maintain their position when the temperature changes, reducing the loss of microorganisms falling off due to temperature fluctuations. Therefore, the present invention improves the life of the preparation in the natural environment through the coordinated use of liquid mixed bacteria and solid adsorption carriers.
[0017] It should also be noted that the solid adsorption carrier used in the present invention is not a simple molecular sieve, but also has a specific ratio of TiO2, ZnO, Cu2O and Fe3O4 photocatalysts. In practical applications, these materials can not only use photocatalysis to degrade plastics, but also produce synergistic effects with microbial strains to promote microbial activity. In particular, the synergistic effect between Fe3O4 and Bacillus ferrooxidans can transfer electrons to Fe3O4 and reduce it to Fe 2+This process not only provides energy for microorganisms, but also helps to degrade plastics, because the electron transfer process may be accompanied by the oxidation of organic matter. The presence of Fe3O4 as an electron acceptor can promote the growth and metabolic activity of A. abalonei, thereby improving its ability to degrade plastics. The reduction process of Fe3O4 may also produce some intermediates, which may further promote the degradation activities of other microorganisms.
[0018] The second aspect of the present invention provides a method for preparing a plastic-degrading composite microbial preparation, comprising the following steps:
[0019] (1) inoculating the activated Bacillus stearothermophilus, Thermus thermophilus, and Bacillus amylophagous into a fermentation medium for fermentation and culturing to obtain bacterial solution 1;
[0020] The ratio of the inoculation number of Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermoamylovorus is (1.5~2):(3~4):1;
[0021] (2) inoculating the activated Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica into a fermentation medium for fermentation and culturing to obtain bacterial solution II;
[0022] The ratio of the inoculation number of Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica was (2-3): (1-5): (1-2): 1;
[0023] (3) Mixing bacterial solution 1 and bacterial solution 2 to obtain liquid bacteria;
[0024] (4) adding a silicon source to an alkaline aqueous solution containing a sodium source and an aluminum source, and mixing to obtain a molecular sieve precursor solution;
[0025] Add TiO2, ZnO, Cu2O and Fe3O4 to the molecular sieve precursor solution and stir evenly, and stir at constant temperatures of 20°C, 40°C and 60°C for 12 to 24 hours to obtain a molecular sieve precursor solution for forming crystal nuclei;
[0026] The molecular sieve precursor solution for forming the crystal nucleus is heated to 90-100°C in a closed reactor for crystallization reaction, and then filtered and dried to obtain a solid adsorption carrier;
[0027] (5) The liquid bacteria and the solid adsorption carrier are mixed in a mass ratio of 1:(1.5-3), and the microbial preparation is obtained after carrier adsorption and drying.
[0028] Preferably, in step (1) and step (2),
[0029] The fermentation medium is composed of the following by mass percentage: 3-5% soy peptone, 5-10% glucose, 3-5% honey, 8-10% corn yeast powder, 0.01-2% dipotassium hydrogen phosphate, 0.01-2% potassium dihydrogen phosphate, 0.01-2% triammonium citrate, 0.2-1% magnesium sulfate and 8-12% rice husk powder, and the balance is water.
[0030] Preferably, in step (1), Bacillus stearothermophilus, Thermus thermophilus and Bacillus amylophagous are fermented in a fermenter, the stirring speed of the fermenter is 30-60 rpm, and the fermentation conditions are: temperature 50-62°C, fermentation time 24-36 hours, dissolved oxygen value DO 3.5-4.5 mg / L, and pH 6-8.
[0031] Preferably, in step (2), Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica are fermented in a fermenter, the stirring speed of the fermenter is 30-60 rpm, and the fermentation conditions are: temperature 25-35°C, fermentation time 48-60 hours, dissolved oxygen value DO 3.0-4.0 mg / L, and pH 6-8.
[0032] Preferably, in step (1) and step (2), during the activation culture process, Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermoamylovorus are inoculated into the first culture medium respectively, and cultured at a shaking speed of 150-160 rpm and 30-40° C. for 24-36 h; Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreduconi and Saccharomyces lipolytica are inoculated into the second culture medium respectively, and cultured at a shaking speed of 150-160 rpm and 25-28° C. for 36-48 h to obtain a primary seed culture solution of a single strain;
[0033] The first culture medium is composed of the following by mass fraction: 0.4-0.6% soy peptone, 0.4-0.6% yeast extract powder, 0.8-1.2% glucose, 1.8-2.2% agar, 0.2-0.4% beef extract, 0.6-1.0% potassium dihydrogen phosphate, 0.6-1.0% dipotassium hydrogen phosphate and 0.06-0.1% manganese sulfate, and the remainder is water; the relative humidity in the first culture medium is 56-60%; the second culture medium is PDA liquid culture medium.
[0034] Preferably, in step (4), the molecular sieve precursor solution is obtained by mixing according to the molar ratio of Na2O:Al2O3:SiO2:H2O=(0.5-0.9):(0.1-0.4):1:(40-80).
[0035] Preferably, in step (4), the mass ratio of SiO2 to TiO2 is (15-20):1.
[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0037] 1. The liquid mixed bacteria in the present invention contain a variety of microorganisms, which play a role in different metabolic pathways and can decompose different components of plastics, thereby improving the overall degradation efficiency.
[0038] 2. The present invention also uses a suitable solid adsorption carrier, which not only helps to maintain the number and activity of microorganisms, but also provides additional catalytic function, further improving the degradation efficiency of the preparation.
[0039] 3. The microorganisms added to the preparation of the present invention are diverse and can play a degradation role under different temperature conditions, which enables the preparation to adapt to changing conditions in the natural environment. At the same time, the presence of the solid carrier also provides a relatively stable microenvironment for the microorganisms, and even if the external conditions change, a certain degradation efficiency can be maintained.
[0040] 4. The present invention utilizes solid adsorption carriers to not only protect microorganisms from adverse external factors, but also help microorganisms adhere to the plastic surface, increase the contact area, and thus improve the degradation efficiency. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] This embodiment provides a plastic-degrading composite microbial preparation, which includes mixed bacteria and a solid adsorption carrier.
[0044] The raw materials of the mixed bacteria include Bacillus stearothermophilus, Thermus thermophilus, Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens, and Saccharomyces lipolytica;
[0045] Bacillus stearothermophilus was purchased from Shanghai Chen Microbiology Technology Co., Ltd. with the number GDMCC 1.301;
[0046] Thermus thermophilus was purchased from Shanghai Chen Microbiology Technology Co., Ltd. with the number CICC 10347;
[0047] Thermomylovora amylovora was purchased from Shanghai Chen Microbiology Technology Co., Ltd., with the number CICC 10143;
[0048] Bacillus amyloliquefaciens was purchased from Shanghai Chen Microbiology Technology Co., Ltd. with the number GDMCC 1.129;
[0049] Bacillus proteolyticus was purchased from Shanghai Chen Microbiology Technology Co., Ltd. with the number GDMCC 800053;
[0050] Bacillus ferroreducens was purchased from Shanghai Chen Microbiology Technology Co., Ltd. with the number GDMCC 1.2107;
[0051] The yeast Saccharomyces lipolytica was purchased from Shanghai Chen Microbiology Technology Co., Ltd. with the code number GDMCC 2.197.
[0052] The solid adsorption carrier includes a molecular sieve and TiO2, ZnO, Cu2O and Fe3O4 uniformly distributed in the molecular sieve. The mass ratio of TiO2, ZnO, Cu2O and Fe3O4 is 1:1:0.6:0.3;
[0053] TiO2 was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XFI02, particle size 5-10 nm;
[0054] ZnO was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-ZNO-01, particle size 20 nm;
[0055] Cu2O was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-Cu2O-01, particle size 500nm;
[0056] Fe3O4 was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd. with the model number of XT-Fe3O4-03 and a particle size of 80 nm.
[0057] The water content of the composite microbial preparation was 25%, and the total bacterial count was 4.56×10 9 cfu / g.
[0058] This embodiment also provides a method for preparing a plastic-degrading composite microbial preparation, comprising the following steps:
[0059] (1) During the activation culture process, Bacillus stearothermophilus, Thermus thermophilus and Bacillus amyloliquefaciens were inoculated into the first culture medium respectively, and cultured at 35°C for 28 h at a shaking speed of 150 rpm to obtain a primary seed culture solution of a single strain; the first culture medium was composed of the following by mass fraction: 0.5% soy peptone, 0.5% yeast extract powder, 1.0% glucose, 2.0% agar, 0.3% beef extract, 0.8% potassium dihydrogen phosphate, 0.8% potassium hydrogen phosphate and 0.08% manganese sulfate, and the balance was water; the relative humidity in the first culture medium was 58%;
[0060] The activated Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermomylophagus were inoculated into the fermentation medium for fermentation culture. The Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermomylophagus were fermented in a fermenter. The stirring speed of the fermenter was 50 rpm. The fermentation conditions were as follows: temperature 55° C., fermentation time 30 hours, dissolved oxygen value DO 4.0 mg / L, pH 6.6, to obtain bacterial solution 1.
[0061] The ratio of the inoculum number of Bacillus stearothermophilus, Thermus thermophilus, and Bacillus thermoamylovorus was 1.8:3.5:1;
[0062] The fermentation medium is composed of the following by mass percentage: 4% soy peptone, 6% glucose, 4% honey, 9% corn yeast powder, 0.1% dipotassium hydrogen phosphate, 0.05% potassium dihydrogen phosphate, 0.03% triammonium citrate, 0.5% magnesium sulfate and 10% rice husk powder, and the balance is water.
[0063] (2) During the activation culture process, Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica were inoculated into the second culture medium respectively, and cultured at 26°C for 40 h at a shaking speed of 145 rpm to obtain a primary seed culture solution of a single strain; the second culture medium was PDA liquid culture medium.
[0064] The activated Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreductus and Saccharomyces lipolytica were inoculated into the fermentation medium for fermentation culture, and the Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreductus and Saccharomyces lipolytica were fermented in a fermenter, the stirring speed of the fermenter was 55 rpm, the fermentation conditions were: temperature 28°C, fermentation time 50 hours, dissolved oxygen value DO 3.5 mg / L, pH 7, to obtain bacterial solution II;
[0065] The inoculation ratio of Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreduconis and Saccharomyces lipolytica was 2.5:2:1.5:1;
[0066] The fermentation medium is composed of the following by mass percentage: 5% soy peptone, 6% glucose, 4% honey, 9% corn yeast powder, 0.05% dipotassium hydrogen phosphate, 0.1% potassium dihydrogen phosphate, 0.5% triammonium citrate, 0.3% magnesium sulfate and 11% rice husk powder, and the balance is water.
[0067] (3) Mix bacterial solution 1 and bacterial solution 2 to obtain liquid bacteria.
[0068] (4) adding a silicon source to an alkaline aqueous solution containing a sodium source and an aluminum source, and mixing to obtain a molecular sieve precursor solution;
[0069] TiO2, ZnO, Cu2O and Fe3O4 were added to the molecular sieve precursor solution and stirred evenly. The mixture was stirred at constant temperatures of 20°C, 40°C and 60°C for 20 hours to obtain a molecular sieve precursor solution for forming crystal nuclei. The molecular sieve precursor solution was obtained by mixing according to a molar ratio of Na2O:Al2O3:SiO2:H2O=0.6:0.3:1:50. The mass ratio of SiO2 to TiO2 was 18:1.
[0070] The molecular sieve precursor solution for forming crystal nuclei is heated to 95° C. in a closed reactor for crystallization reaction, and a solid adsorption carrier is obtained after filtering and drying.
[0071] (5) The liquid bacteria and the solid adsorption carrier are mixed in a mass ratio of 1:2, and the microbial preparation is obtained after the carrier adsorption and drying.
[0072] Example 2
[0073] The difference between this embodiment and embodiment 1 is that the composition of the plastic-degrading composite microbial preparation is different.
[0074] In this embodiment, the ratio of the inoculated number of Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermoamylovorus is 1.5:4:1;
[0075] The inoculation ratio of Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreduconis and Saccharomyces lipolytica was 2:3.5:1:1;
[0076] The solid adsorption carrier comprises a molecular sieve and TiO2, ZnO, Cu2O and Fe3O4 uniformly distributed in the molecular sieve, wherein the mass ratio of TiO2, ZnO, Cu2O and Fe3O4 is 1:1:0.5:0.4.
[0077] The water content of the composite microbial preparation was 23%, and the total bacterial count was 3.44×10 9 cfu / g.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that the inoculated amount of bacteria is different.
[0080] In this comparative example, the ratio of the inoculation numbers of Bacillus stearothermophilus, Thermus thermophilus and Bacillus amylolyticus is 1.5:4:3; the inoculation numbers of Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreduconi and Saccharomyces lipolytica are 2:3.5:1:3.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that the raw material of the mixed bacteria does not contain Thermus thermophilus.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is that the raw material of the mixed bacteria does not contain Bacillus amyloliquefaciens.
[0085] Comparative Example 4
[0086] The difference between this comparative example and Example 1 is that the raw material of the mixed bacteria does not contain A. abalonei.
[0087] Comparative Example 5
[0088] The difference between this comparative example and Example 1 is that no mixed bacteria are added to the plastic-degrading composite microbial preparation, and the solid adsorption carrier is directly used as the plastic-degrading preparation.
[0089] Comparative Example 6
[0090] The difference between this comparative example and Example 1 is that TiO2, ZnO, Cu2O and Fe3O4 are not added to the solid adsorption carrier, and the molecular sieve is directly used as the solid carrier.
[0091] The preparation method of the molecular sieve in this comparative example is:
[0092] Adding a silicon source into an alkaline aqueous solution containing a sodium source and an aluminum source, and mixing to obtain a molecular sieve precursor solution;
[0093] The molecular sieve precursor solution was stirred at constant temperature for 20 hours at 20° C., 40° C. and 60° C. respectively to obtain a molecular sieve precursor solution for forming a crystal nucleus; the molecular sieve precursor solution was obtained by mixing according to a molar ratio of Na2O:Al2O3:SiO2:H2O=0.6:0.3:1:50;
[0094] The molecular sieve precursor solution for forming crystal nuclei is heated to 95° C. in a closed reactor for crystallization reaction, and the molecular sieve is obtained after filtering and drying.
[0095] Comparative Example 7
[0096] The difference between this comparative example and Example 1 is that TiO2 is not added to the solid adsorption carrier.
[0097] Comparative Example 8
[0098] The difference between this comparative example and Example 1 is that no Fe3O4 is added to the solid adsorption carrier.
[0099] Comparative Example 9
[0100] The difference between this comparative example and Example 1 is that the mass ratio of TiO2, ZnO, Cu2O and Fe3O4 is 1:1:0.6:1.
[0101] Comparative Example 10
[0102] The difference between this comparative example and Example 1 is that the mixed bacteria are directly applied to the plastic degradation preparation.
[0103] Performance Testing
[0104] The collected soil was mixed with the crushed PE film. After testing, the pH value of the soil was 7.2, the organic matter content was 5%, the salt content was 0.8 dS / m, the mass of the PE film was 0.01% of the soil mass, the thickness of the PE film was 30 microns, and the size was about 10 cm×10 cm. Then the preparations prepared in the embodiments and comparative examples were added to the mixture of the above soil and PE film for mixing. The amount of the preparation added was 8% of the mass of the mixture. Then the moisture content was adjusted to 60%. Under the conditions of natural light illumination and humidity of 60% RH, the soil was piled up at room temperature, 45 degrees Celsius and -30 degrees Celsius, respectively, and the pile was turned every seven days. A blank control was set up, and no preparation was added to the control group. The content of PE plastic was measured after 60 days.
[0105] Plastic degradation rate = (mass of PE film added to the soil - mass of PE film after preparation treatment) / mass of PE film added to the soil × 100%.
[0106] The performance test results are shown in Table 1.
[0107] Table 1 Plastic degradation performance test results
[0108] ;
[0109] It can be seen from the above performance test results that the plastic degradation efficiency of Examples 1-2 and the maintenance effect of the plastic degradation efficiency under different environments are both good, especially the comprehensive performance of Example 1 is the most outstanding. This is mainly because the present invention designs the strain of liquid mixed bacteria and specifically adds a solid adsorption carrier with a photocatalyst. The liquid mixed bacteria and the solid adsorption carrier work synergistically, which not only improves the degradation efficiency of the preparation, but also improves the environmental resistance of the preparation.
[0110] However, the comparative examples were significantly inferior to the examples in the corresponding performance tests because they did not adopt the necessary technical solutions. In comparative example 1, the addition amount of various strains in the liquid mixed bacteria was changed. From the results, it can be seen that the plastic degradation effect decreased, proving that the specific addition amount of each strain in the present invention has a certain degree of influence on improving the degradation efficiency and environmental resistance of the preparation. In comparative examples 2 and 3, Thermus thermophilus and Bacillus amyloliquefaciens were not added respectively. From the results, it can be seen that the plastic degradation effect of the preparation further decreased, which had a more serious impact on the synergistic effect of the seven strains in the present invention, indicating that the liquid mixed bacteria composed of seven strains in the present invention has an important influence on improving the comprehensive performance of the preparation. In Comparative Example 4, no Bacillus iron-reducing bacteria were added. This strain had a synergistic effect with the ferroferric oxide in the solid adsorption carrier. From the results, it can be seen that the comprehensive performance of the preparation prepared by it further decreased, indicating that the Bacillus iron-reducing bacteria in the present invention not only produced a synergistic effect with other strains in the liquid mixed bacteria, but also produced another common effect with ferroferric oxide, thereby having an important impact on the degradation effect and environmental resistance of the preparation. In Comparative Example 5, the solid adsorption carrier was directly used as a preparation for plastic degradation. From the results, it can be seen that the plastic degradation effect was significantly reduced, indicating that the simultaneous use of the liquid mixed bacterial agent and the photocatalytic effect in the present invention has an important impact on improving the comprehensive performance of the preparation. In Comparative Example 6, no photocatalyst was added to the solid adsorbent, but the molecular sieve was used as a carrier to provide a fixation effect for the liquid mixed bacteria. From the results, it can be seen that the comprehensive performance of the preparation was significantly reduced, indicating that the use of the photocatalyst has an important impact on improving the comprehensive performance of the preparation. In both Comparative Examples 7 and 8, the use of one catalyst was reduced. From the results, it can be seen that the degradation effect and environmental resistance of the preparations decreased to varying degrees, indicating that the use of the photocatalyst composition has an important influence on improving the comprehensive performance of the preparation. In Comparative Example 9, the ratio of the four catalysts was changed. From the results, it can be seen that the comprehensive performance of the preparation was affected to a certain extent, indicating that the catalyst composition has an important influence on improving the comprehensive performance of the preparation. In Comparative Example 10, the liquid mixed bacteria were directly used as a preparation to degrade plastic. From the results, it can be seen that although the degradation efficiency of the preparation was improved compared with the control group, the degradation efficiency was significantly reduced compared with the embodiment, indicating that the liquid mixed bacteria and the solid adsorption carrier in the present invention have a synergistic effect, and can work together to improve the comprehensive performance of the preparation. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
[0111] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A plastic-degrading composite microbial preparation, characterized in that: The plastic-degrading composite microbial preparation includes mixed bacteria and a solid adsorption carrier; The raw materials of the mixed bacteria include Bacillus stearothermophilus, Thermus thermophilus, Bacillus thermomylovora, Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica; The solid adsorption carrier includes a molecular sieve and TiO2, ZnO, Cu2O and Fe3O4 distributed in the molecular sieve; wherein the mass ratio of TiO2, ZnO, Cu2O and Fe3O4 is 1:1: (0.5-0.8): (0.2-0.4).
2. A plastic-degrading composite microbial preparation according to claim 1, characterized in that: The water content of the composite microbial preparation is less than 28%, and the total bacterial count is greater than 2.5×10 9 cfu / g.
3. A method for preparing a plastic-degrading composite microbial preparation according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) inoculating the activated Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermoamylovorus into a fermentation medium for fermentation and culturing to obtain bacterial solution 1; The ratio of the inoculation number of Bacillus stearothermophilus, Thermus thermophilus and Bacillus thermoamylovorus is (1.5~2):(3~4):1; (2) inoculating the activated Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica into a fermentation medium for fermentation and culturing to obtain bacterial solution II; The ratio of the inoculation number of Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica was (2-3): (1-5): (1-2): 1; (3) Mixing bacterial solution 1 and bacterial solution 2 to obtain liquid bacteria; (4) adding a silicon source to an alkaline aqueous solution containing a sodium source and an aluminum source, and mixing to obtain a molecular sieve precursor solution; Add TiO2, ZnO, Cu2O and Fe3O4 to the molecular sieve precursor solution and stir evenly, and stir at constant temperatures of 20°C, 40°C and 60°C for 12 to 24 hours to obtain a molecular sieve precursor solution for forming crystal nuclei; The molecular sieve precursor solution for forming the crystal nucleus is heated to 90-100°C in a closed reactor for crystallization reaction, and then filtered and dried to obtain a solid adsorption carrier; (5) The liquid bacteria and the solid adsorption carrier are mixed in a mass ratio of 1:(1.5-3), and the microbial preparation is obtained after carrier adsorption and drying.
4. The method for preparing a plastic-degrading composite microbial preparation according to claim 3, characterized in that: In step (1) and step (2), The fermentation medium is composed of the following by mass percentage: 3-5% soy peptone, 5-10% glucose, 3-5% honey, 8-10% corn yeast powder, 0.01-2% dipotassium hydrogen phosphate, 0.01-2% potassium dihydrogen phosphate, 0.01-2% triammonium citrate, 0.2-1% magnesium sulfate and 8-12% rice husk powder, and the balance is water.
5. The method for preparing a plastic-degrading composite microbial preparation according to claim 3, characterized in that: In step (1), Bacillus stearothermophilus, Thermus thermophilus and Bacillus amylophagous thermophilus are fermented in a fermenter, the stirring speed of the fermenter is 30-60 rpm, the fermentation conditions are: temperature 50-62°C, fermentation time 24-36 hours, dissolved oxygen value DO 3.5-4.5 mg / L, pH 6-8.
6. The method for preparing a plastic-degrading composite microbial preparation according to claim 3, characterized in that: In step (2), Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreducens and Saccharomyces lipolytica are fermented in a fermentation tank, the stirring speed of the fermentation tank is 30-60 rpm, the fermentation conditions are: temperature 25-35°C, fermentation time 48-60 hours, dissolved oxygen value DO 3.0-4.0 mg / L, pH 6-8.
7. The method for preparing a plastic-degrading composite microbial preparation according to claim 3, characterized in that: In step (1) and step (2), during the activation culture process, Bacillus stearothermophilus, Thermus thermophilus and Bacillus amylolyticus are inoculated into the first culture medium respectively, and cultured at a shaking speed of 150-160 rpm and 30-40° C. for 24-36 hours; Bacillus amyloliquefaciens, Bacillus proteolyticus, Bacillus ferroreduconi and Saccharomyces lipolytica are inoculated into the second culture medium respectively, and cultured at a shaking speed of 150-160 rpm and 25-28° C. for 36-48 hours to obtain a primary seed culture solution of a single bacterial species; The first culture medium is composed of the following by mass fraction: 0.4~0.6% soy peptone, 0.4~0.6% yeast extract powder, 0.8~1.2% glucose, 1.8~2.2% agar, 0.2~0.4% beef extract, 0.6~1.0% potassium dihydrogen phosphate, 0.6~1.0% dipotassium hydrogen phosphate and 0.06~0.1% manganese sulfate, and the balance is water; the relative humidity in the first culture medium is 56~60%; the second culture medium is PDA liquid culture medium.
8. The method for preparing a plastic-degrading composite microbial preparation according to claim 3, characterized in that: In step (4), a molecular sieve precursor solution is obtained by mixing according to a molar ratio of Na2O:Al2O3:SiO2:H2O=(0.5-0.9):(0.1-0.4):1:(40-80).
9. The method for preparing a plastic-degrading composite microbial preparation according to claim 8, characterized in that: In step (4), the mass ratio of SiO2 to TiO2 is (15-20):1.
Citation Information
Patent Citations
High efficiency decontamination additive comprising metal oxide nanoparticles in metal or semi-metal nanoparticle matrix, paints, formulations and like for addition to protection, coating or decoration of soft or hard surfaces
CN118019583A
A biodegradable plastic composition
KR101307194B1